Nonlinear Finite Element Modeling of Red Meranti Compression at an Angle to the Grain - Yosafat A. Pranata; Bambang Suryoatmono (Journal of Engineering and Technological Sciences, 2013)
In an orthotropic material, the grain angle has a significant influence on its mechanical properties. The aim of this research was to perform a numerical simulation using a nonlinear finite element analysis (FEA) to obtain the compression strength of the Red Meranti (shorea spp.) timber species at an angle to the grain ranging from 12° to 80°. The material properties needed for the analysis were obtained from clear specimen tests. To investigate the validity of the numerical results, various cross grain specimens were tested under uniaxial compressive stress. It has been shown in this study that an FEA based on the distortion energy of an orthotropic material can be used to obtain the compressive strength at proportional limit for cross grain specimens. Compa-rison with the experimental results showed that for a cross grain angle between 12° and 80° the FEA predicted the strength to be 9.4% to 33.6% lower than the experimental results. Compared to using Hankinson's formula to predict the compressive strength at a cross grain angle, using the FEA always gave a lower value, ranging from 13.2% to 30.5%. Based on these results, an FEA incorporating Hill's yield criterion is a conservative method for predicting compressive strength at an angle to the grain.